Penentuan Derajat Toksisitas Akut Ekstrak Air Buah Pepaya (Carica papaya L.) Muda Pada Mencit Menggunakan Purposed New Recommended Method - Nadiyah, Laila Dinda; Kharisma, Yuktiana; Yuniarti, Yuniarti (Jurnal Jamu Indonesia, 2016)
Papaya (Carica papaya L.) fruit was proven scientifically in having medicinal effects: such as gastroprotective, laxative, galactagogues, and antibacterial effect. Unripe papaya fruit contains saponin, alkaloid, tannin, flavonoid, triterpenoid, and quinone which may reveal toxicities as adverse effect when it consumed in high dose. The aim of this study is to determine the acute toxicity degree of unripe Carica papaya L. fruit aqueous extract in mice using proposed new recommended method. The acute toxicity degree conducted by determination of lethal dose50 (LD50) using new recommended method to 12 female mice. The subjects were divided into three stages and each mouse was given different dose of the extract. LD50 calculated by mean of mortality lowest dose and non mortality highest dose then the result classified into the degree of acute toxicity. The study showed there was no mortality in all groups of the experimental subject. LD50 of unripe Carica papaya L. aqueous extract was found >5000 mg/kg BW and classified as Practically Non Toxic (PNT) substance.